2011
DOI: 10.1111/j.1749-124x.2011.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural–urban Migration and Dynamics of Income Distribution in China: A Non–parametric Approach

Abstract: Extending the income dynamics approach in Quah (2003), the present paper studies the enlarging income inequality in China over the past three decades from the viewpoint of rural–urban migration and economic transition. We establish non‐parametric estimations of rural and urban income distribution functions in China, and aggregate a population‐weighted, nationwide income distribution function taking into account rural–urban differences in technological progress and price indexes. We calculate 12 inequality inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
(24 reference statements)
0
10
0
3
Order By: Relevance
“…. Rural to urban labor migration not only provides migrant workers with more employment opportunities and higher wages (Liu and Zou, 2011;Li et al, 2013), but has also changed the demographic composition of rural China. In particular, it has created a generation of children who remain in the countryside with a s urrogate caregiver when their parents migrate for work (Duan and Zhou, 2005;Ye et al, 2006;Zhan et al, 2014).…”
mentioning
confidence: 99%
“…. Rural to urban labor migration not only provides migrant workers with more employment opportunities and higher wages (Liu and Zou, 2011;Li et al, 2013), but has also changed the demographic composition of rural China. In particular, it has created a generation of children who remain in the countryside with a s urrogate caregiver when their parents migrate for work (Duan and Zhou, 2005;Ye et al, 2006;Zhan et al, 2014).…”
mentioning
confidence: 99%
“…Although the importance of understanding the inequality in industrial output is well established, no research has been conducted to study the distribution dynamics of industrial output at the county-level. In fact, many researchers have employed distribution dynamics approach in studying convergence and evolution of different economic characteristics in China (He & Zhang, 2007;He, 2010;Herrerías, 2012;Herrerías, et al, 2010;Herzfeld, 2008;Ho & Li, 2006Li, 2003;Liao & Wei, 2012;Liu & Zou, 2011;Pu, et al, 2005;Sakamoto & Fan, 2010Sakamoto & Islam, 2008;Villaverde & Maza, 2012;Villaverde, et al, 2010;Wang, 2011;Wang & Zhu, 2013;Wei & Ye, 2009;Zhou & Zou, 2010;Zhu, et al, 2008). However, most of these researchers have focused on the inequality in per capita income or GDP, though some of them have employed distribution dynamics analysis in studying the inequality in other socioeconomic issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…() found that reducing roading inequality would lead to a reduction of income inequality. Infrastructure investment, particularly in the rural areas, could facilitate rural–urban migration and achieve more rapid technological progress in the rural sector (Liu and Zou, ).…”
Section: Suggested Interventionsmentioning
confidence: 99%